Risk factors for death among critically ill patients with acute renal failure - Silva Júnior, Geraldo Bezerra da; Daher, Elizabeth De Francesco; Mota, Rosa Maria Salani; Menezes, Francisco Albano (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Acute renal failure is a common medical problem, with a high mortality rate. The aim of this work was to investigate the risk factors for death among critically ill patients with acute renal failure. DESIGN AND SETTING: Retrospective cohort at the intensive care unit of Hospital Universitário Walter Cantídio, Fortaleza. METHODS: Survivors and non-survivors were compared. Univariate and multivariate analy- ses were performed to establish risk factors for death. RESULTS: Acute renal failure occurred in 128 patients (33.5%), with mean age of 49 ± 20 years (79 males; 62%). Death occurred in 80 (62.5%). The risk factors most frequently as- sociated with death were hypotension, sepsis, nephrotoxic drug use, respiratory insufficiency, liver failure, hypovolemia, septic shock, multiple organ dysfunction, need for vasoactive drugs, need for mechanical ventilation, oliguria, hypo- albuminemia, metabolic acidosis and anemia. There were negative correlations between death and: prothrombin time, hematocrit, hemoglobin, systolic blood pressure, diastolic blood pressure, arterial pH, arterial bicarbonate and urine vol- ume. From multivariate analysis, the independent risk factors for death were: need for mechanical ventilation (OR = 3.15; p = 0.03), hypotension (OR = 3.48; p = 0.02), liver failure (OR = 5.37; p = 0.02), low arterial bicarbonate (OR = 0.85; p = 0.005), oliguria (OR = 3.36; p = 0.009), vasopressor use (OR = 4.83; p = 0.004) and sepsis (OR = 6.14; p = 0.003). CONCLUSIONS: There are significant risk factors for death among patients with acute renal failure in intensive care units, which need to be identified at an early stage for early treatment.